The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/rapm-2019-100964
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of the erector spinae plane block: distribution of dye in a porcine model

Abstract: This study aimed to describe the anatomical distribution of dye injected in the erector spinae plane (ESP) in a porcine living model, which could aid to reveal factors potentially relevant to the unexplained clinical effects of the ESP block. Six pigs received 0.6 mL/kg of 0.25% new methylene blue at the level of the sixth thoracic vertebra through either a cranial-to-caudal or a caudal-to-cranial in-plane ultrasound-guided bilateral ESP injection 20 min before euthanasia.Spread of dye evaluated through transv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…Most cadaveric studies examining the spread of ESPB have shown extensive longitudinal and lateral spread of dye deep and superficial to and inside the erector spinae muscles, but little spread to the paravertebral space that is the main target of TPVB because that area includes both the ventral and dorsal rami of the thoracic nerves. [18][19][20][21][22][23] One of the most apparent advantages of ESPB is its lower demand for technical expertise. We showed that ESPB was performed in a shorter period of time than TPVB, as previous studies have shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cadaveric studies examining the spread of ESPB have shown extensive longitudinal and lateral spread of dye deep and superficial to and inside the erector spinae muscles, but little spread to the paravertebral space that is the main target of TPVB because that area includes both the ventral and dorsal rami of the thoracic nerves. [18][19][20][21][22][23] One of the most apparent advantages of ESPB is its lower demand for technical expertise. We showed that ESPB was performed in a shorter period of time than TPVB, as previous studies have shown.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Injectate administered by ESPB is expected to make a wide spread in the craniocaudal direction, yet the results of cadaveric studies show inconsistent and unpredictable dye spread with little spread to the paravertebral space. [18][19][20][21][22][23] Accordingly, this retrospective propensity-matched study was conducted to see if ESPB could provide comparable analgesic effects to TPVB in patients undergoing breast surgery using data saved in our departmental registry. We also compared the distribution of sensory blockade after TPVB and ESPB.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have raised concerns and objections. Otero PE et al [24] according to inject dye in the erector spinae plane in a porcine living model, found there is no evidence of anterior spread of dye involving thoracic paravertebral or epidural spaces. The cadaver study by Ivanusic et al [25] also demonstrated that there was no spread of dye anteriorly to the paravertebral space to involve the origins of the ventral and dorsal branches of the thoracic spinal nerves.…”
Section: Fig 2 Marked Lines and Pointsmentioning
confidence: 98%
“…The diffusion of local anesthetic drugs in the thoracolumbar fascia helps to modulate the somatic and visceral pain. Recently, Otero PE et al [24] found that the thoracic lymph nodes were stained when exploring the mechanism of ESP block in a porcine model. They considered it might be that the local anesthesia entered the lymphatic reflux and desensitized the sensory nerve fibers connected to the lymphatic finger, contributing to clinical analgesic effects.…”
Section: Fig 2 Marked Lines and Pointsmentioning
confidence: 99%
“…documented the absence of solution spread into the paravertebral area in a cadaveric study, Adhikary et al 19 stated that the solution they used reached both the epidural and paravertebral areas. Also, Otero et al 20 reported a new perspective on the ESPB efficacy mechanism. They injected six pigs with dye using the ESPB technique at the T6 level while they were alive and sacrificed them after 20 minutes to evaluate the distribution of the dye by studying the cadavers.…”
Section: Discussionmentioning
confidence: 99%